The effectiveness of entrepreneursip teaching materials for engginering students at the faculty of engineering, semarang state university - Rachmawati, Rina (Dinamika Pendidikan, 2016)
The objective of the was to test the effectiveness of entrepreneurship teaching materials for students majoring at Pendidikan Kesejahteraan keluarga (PKK) on the Faculty of Engineering, Semarang State University (Unnes). Entrepreneurship teaching materials were developed by researchers with ADDIE model, and the article only focused on the effectiveness of entrepreneurship teaching materials. It was a quasi-experimental study with a before-after or one group pretest-posttest technique. The research was conducted for 4th semester students of Pendidikan Kesejahteraan Keluarga (PKK) Department who were taking the entrepreneurship subject. In the experimental group, students were taught with teaching materials which were developed by the references of entrepreneurship subject on Higher Education and also was adapted with the conditions ofÂ  Unnes students.The data were collected by test, questionnaires and learning observation sheets. To test the hypothesis, it used paired t-test analysis and gain-score testing to measure the effectiveness of teaching materials in supporting the Entrepreneurship subject at the department of PKK on the Faculty of Engineering, Unnes. The results of the study showed that entrepreneurship teaching materials were in enough effective and the results of other analyzes showed that studentsâ scores increased from pre-test to post-test for students who were taught with Entrepreneurship teaching materials.